THE EVOLUTION OF INFORMAL SPEECH: HOW LANGUAGE CHANGES IN EVERYDAY CONVERSATIONS (Web of Teachers: Inderscience Research, 2025)
This article explores the evolution of informal speech, focusing on how language transforms in everyday conversations. Informal speech is a dynamic aspect of language that reflects social, cultural, and technological shifts. By analyzing trends such as the rise of slang, abbreviations, digital communication's impact, and the increasing informality of professional settings, the article traces how informal language adapts over time. It also delves into the role of regional dialects, globalization, and media influence in shaping conversational language. The study provides insights into how language functions as a living entity, constantly reshaped by its users in various social contexts.